The Multifaced Actions of Curcumin in Pregnancy Outcome - Giovanni Tossetta; Sonia Fantone; Stefano Raffaele Giannubilo; Daniela Marzioni (MDPI AG, 2021)
Curcumin, also known as diferuloylmethane, is the main polyphenolic substance present in the rhizomes of Curcuma longa L. This plant showed many beneficial effects and has been used since ancient times for both food and pharmaceutical purposes. Due to its pleiotropic functions, curcumin consumption in the human diet has become very common thanks also to the fact that this natural compound is considered quite safe as it does not have serious side effects. Its functions as an anti-inflammatory, anti-oxidant, neuroprotective, immunomodulatory, anti-toxicant, anti-apoptotic, and anti-diabetic compound are already known and widely demonstrated. There are numerous studies concerning its effects on various human pathologies including cancer, diabetes and arthritis while the studies on curcumin during pregnancy have been performed only in animal models. Data concerning the role of curcumin as anti-inflammatory compound suggest a possible use of curcumin in managing pregnancy complications such as Preeclampsia (PE), Gestational Diabetes Mellitus (GDM), Fetal Growth Restriction (FGR), PreTerm Birth (PTB), and exposure to toxic agents and pathogens. The aim of this review is to present data to support the possible use of curcumin in clinical trials on human gestation complications.